Different patient subgroup, different ranking? Which quality indicators do patients find important when choosing a hospital for hip- or knee arthroplasty? - Zwijnenberg Nicolien C; Damman Olga C; Spreeuwenberg Peter; Hendriks Michelle; Rademakers Jany JDJM (BMC, 2011)
Abstract Background Patients are increasingly expected to become active, critical consumers in healthcare. They can use comparative healthcare information presented on websites to make informed choices for healthcare providers. However, the use of this information has been limited so far. An obstacle can be that the information is not perceived as relevant by patients. Presenting only the most important quality indicators might improve the usefulness of this information. The aim of this study was to explore which quality indicators different subgroups of patients find important when choosing a hospital for total hip arthroplasty (THA) or total knee arthroplasty (TKA). Methods In this explorative, cross-sectional study, questionnaires were distributed to 265 patients who underwent or had to undergo THA/TKA. Participants were asked to rank the importance of three types of quality indicators: patient experience indicators, clinical performance indicators, and indicators about hospital services. We used random effects regression analyses to assess the relative importance of the indicators in different subgroups of patients. Results 110 patients (response rate 41.5%) who underwent or had to undergo THA/TKA participated. Conduct of doctors, the presence of procedures to prevent adverse effects of thrombosis and information about the specialist area of orthopaedists were the most important patient experience indicator, clinical performance indicator and indicator about hospital services, respectively. We found a few differences between patient subgroups in the importance attached to the quality indicators. Conclusions This study provides a first insight into which quality indicators patients find important when choosing a hospital for THA/TKA, and shows that subgroups of patients differ in the value they attach to these indicators. More extended research is needed to establish the indicators that should at least be presented in succinct overviews of comparative healthcare information for patients choosing a hospital for THA/TKA.